2012
DOI: 10.4314/ajtcam.v9i4.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crude Aqueous and Alcohol Extracts of <em>Aloe Vera</em> on Growth and Abdominal Viscera of Suckling Rats

Abstract: The gastrointestinal tract of neonates is sensitive to dietary manipulations. When nursing mothers use Aloe vera, their babies are at risk of indirect exposure to Aloe vera via breast feeding or directly as health supplements. The effects of orally administered extracts of Aloe vera in unweaned rats were investigated. Six day old Sprague-Dawley rats were gavaged with aqueous or alcohol extracts of Aloe vera (low dose 50mg. kg -1 or high dose 500mg. kg) daily for eight days. All data were expressed as mean ± SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Our data highlight for the first time, to our knowledge, the protective effects of Aloe vera leaf extract on serum CEA level enhancement induced by immobilization stress. In line with this finding, studies have found that Aloe vera extract has a protective role in different organs [29].…”
Section: Discussionsupporting
confidence: 56%
“…Our data highlight for the first time, to our knowledge, the protective effects of Aloe vera leaf extract on serum CEA level enhancement induced by immobilization stress. In line with this finding, studies have found that Aloe vera extract has a protective role in different organs [29].…”
Section: Discussionsupporting
confidence: 56%
“…Beya et al. () observed enlargement of the caecum in growing rats exposed to high doses of Aloe vera extracts, while Erlwanger and Cooper () reported caecal enlargement in growing rats exposed to high aqueous doses of the African potato extracts. It is interesting to note that the apparent positive effects of M. oleifera leaf powder on GIT organs development were not supported by histology (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Lowering LDL, increasing HDL, decreasing blood glucose level, treating genital herpes and psoriasis [45], positive effect on body mass, caecum and tibial bones in the short term [46], antiinflammatory activity [47].…”
Section: Allium Sativum Influenza and Hypertension Hypertensionmentioning
confidence: 99%